Y = - 5x / 3 + 60
that's your answer!
Step-by-step explanation:
5x-4=-3-x
5x+x=4+(-3)
6x=1
x=1/6
Answer:
1295/36
Step-by-step explanation:
the statement tell us:
(7-(5/6))*(7-(7/6))
we have:
(7-(5/6))=((6*7)-5)/6=(42-5)/6=37/6
and we have:
(7-(7/6))=((6*7)-7)/6=(42-7)/6=35/6
we need multiply both terms:
(37/6)*(35/6)=(37*35)/(6*6)
finally we have
1295/36
This question is false, there are no solutions, even if u take away the x and make it multiplication instead of a variable, still no solutions exist
Answer:
x = 2
y = -3
Step-by-step explanation:
The given equation is,
22(x + yi) + (28 + 4i) = 72 - 62i
By solving this equation further,
22x + 22yi + 28 + 4i = 72 - 62i
(22x + 28) + (22y + 4)i = 72 - 62i
Now both the sides of the equation is in the form of complex number,
By comparing real and imaginary parts given on both the sides,
22x + 28 = 72
22x = 72 - 28
22x = 44
x = 2
22y + 4 = -62
22y = -62 - 4
22y = -66
y = -3
Therefore, x = 2 and y = -3 are the values for which the given equation is true.